A construção da autonomia a partir das vivências dos usuários, familiares e profissionais de um centro de atenção psicossocial (CAPS) - Kammer, Katharina Pereira (2018)
The Psychosocial Care Centers (CAPS) are devices of the mental health policy responsible for assisting users in intense psychic suffering and offer individualized and unique clinical care to population through several actions. However, despite of important advances in the formulation of public policies on mental health and the installation of the substitute network, with devices such as CAPS, the total disruption to the caregiving logic must be fulfilled. The compliance of the precepts of psychiatric reform especially regarding autonomy and deinstitutionalization of users may not be assured. This study aims to analyze the conceptions and meanings of autonomy in daily care of a Psychosocial Care Center (CAPS), based on the experiences of professionals, family members and users. It was a qualitative, cross-sectional and exploratory study carried out in a CAPS in the southern region of Rio Grande do Sul. We interviewed 6 CAPS professionals, 6 service users and 3 family members, based on a semi-structured script. The analysis was based on the analysis of thematic content from three thematic axes: 1) Sense of Autonomy from the experiences of users, family and professionals; 2) Practices of building autonomy in the daily work of CAPS; and 3) Fragilities and potentialities in the process of building autonomy. The main results refer to the diverse understandings related to the concept of autonomy, related to the management of life, independence and self-sufficiency, and as a process in movement, built from relationships, spaces and institutions. The overt understandings have a deep relationship with the life histories of the subjects and allow to demonstrate the autonomy as a power for the expansion and diversification of the relations, from the perspective of care in freedom, instigating the action of the professionals and adding this horizon to the care offered to the users of CAPS.